The economic impact of dry port investment in Indonesia: A case study of Bangil, Pasuruan District, East Java Province - Bambang Eko Afiatno; Karno Dwi Joyoutomo (Cleaner Logistics and Supply Chain)
Acknowledging the pivotal role of ports and dry ports in shaping a nation’s economic landscape, this study explores the economic impact of port development in East Java, specifically Bangil Dry Port in Pasuruan over at least 30 years of business operational process. This study pioneers the quantification of gross value added, investment multiplier effect, tax contribution, and Creating Shared Value (CSV) resulting from dry port investment. The method used for calculating multiplier investment is Keynesian multiplier approach and for labor absorption is Incremental Labor Output Ratio (ILOR). Field surveys were conducted to determine the condition of Bangil, and secondary data on the growth of container flows at Port of Tanjung Perak was used as a reference for growth in Bangil. Overall, these results show that Bangil Dry Port investment will generates positive impact both for government and society in general, but also the economy of East Java and Pasuruan District in particular. These results offer practical guidance for decision-makers in optimizing public funds allocation, while also laying the groundwork for future scholars to conduct comprehensive societal-scale cost-benefit analyses of strategic port investments, contributing to a deeper understanding of the economic implications.